Application of Data Integrity Algorithm for Geotechnical Data Quality Management - Chafiq, Tarik; Ouadoud, Mohammed; Jarar Oulidi, Hassane; Fekri, Ahmed (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The aim of this research work is to ensure the integrity and correction of the geotechnical database which contains anomalies. These anomalies occurred mainly in the phase of inputting and/or transferring of data. The algorithm created in the framework of this paper was tested on a dataset of 70 core drillings. In fact, it is based on a multi-criteria analysis qualifying the geotechnical data integrity using the sequential approach. The implementation of this algorithm has given a relevant set of values in terms of output; which will minimalize processing time and manual verification. The application of the methodology used in this paper could be useful to define the type of foundation adapted to the nature of the subsoil, and thus, foresee the adequate budget.